Procedure to Determine the Relationship Between University Identity and Academic Engagement in Students (Revista científica Olimpia, 2026)
The present study aimed to design and validate a procedure to determine the relationship between university identity and academic engagement among students. A quantitative, cross-sectional, and instrumental approach was employed, grounded in the analytical-synthetic and systemic-structural methods, which enabled the decomposition, contextualization, and integration of the core constructs. The initial design and validation of the procedure were carried out with the support of artificial intelligence tools and expert judgment, facilitating the development of a structured survey through the Google Forms platform, using Likert-type scales adapted to the institutional context. To analyze the relationship between the dimensions of identity and engagement, the non-parametric Spearman correlation test was selected. The designed procedure overcomes previous theoretical limitations and provides valid and relevant instruments for decision-making in the university setting.
Keywords: University identity, Academic engagement, Instrument validation, Artificial intelligence, Spearman correlation